Analysis of Factors Causing Problematic Financing at the Bank Tabungan Negara Syariah KCP Indramayu - Hendri Cahyono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
In providing services to the public, banks develop various banking products and services, one of which is lending funds in the form of financing. The provision of fees contains risks for smooth implementation. Banks carry out good financing methods to minimize the occurrence of problematic financing. Problem financing can have bad consequences if it occurs continuously and will increase if the settlement is not carried out properly. The purpose of this study is to find out and analyze what factors cause problematic financing at BTN Syariah KCP Indramayu and what steps are taken by the bank to solve it. This study uses a qualitative approach method. The results or findings in this study are that the factors causing problematic financing at BTN Syariah KCP Indramayu are from the character of the customer and it reaches 90%, where the customer underestimates the installments that are his obligations. Efforts made by banks are to be more careful in choosing and selecting prospective customers and if there is a financing problem the actions that can be taken are by: rescheduling, reconditioning and restructuring. The conclusion in this study is that credit financing and other products at the BTN Syariah KCP Indramayu bank are still relatively normal and can still be overcome. This can be seen from the problematic financing, which occurs in a small percentage, not up to 1%, or around 0.5%.